Faktor-Faktor Perbedaan Individual dalam Keahlian End-User Computing - Suryandari, Erni (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
The successful application of an information system will be affected by the system itself and executors. Personnel involved in a system covering end-user computing with varying levels of expertise. Computer skills is one of the factors associated with successful implementation of information systems sutu given the importance of these skills, necessary support for the development of such expertise. Factors individual differences associated with computer expertise. Harrison and Rainer (1992) grouping of individual differences into demographics, personality, cognitive style. The discussion is based on the literature and some of the results of empirical studies are concerned. The purpose of this paper is to show some evidence of the existence of various factors related to the EUC expertise involved in the application of accounting information system. The implications of the problem could provide insight for the development of a system and encourage further research.